Blood and urinary variables in horses supplemented with electrolytes - Martins, J. A. (2014)
This study was designed to evaluate changes on variables in blood, urine and water balance in horses in response to a single dose of electrolyte supplementation. The essay was conducted on a randomised 3×3 Latin Square design repeated over time, with three animals and three treatments: Treatment 1: control group (without supplementation); Treatment 2: supplementation with a medium dose of electrolytes composed of: 0.25 g of NaCl + 0.125 g of KCl + 0.05 g of CaCl + 0.025 g of MgCl per kg of BW; Treatment 3: supplementation with a high dose of electrolytes composed of: 0.625 g of NaCl + 0.3125 g of KCl + 0.125 g of CaCl + 0.0625 g of MgCl per kg of BW, equivalent to 2.5 times the medium dose of supplementation. The electrolytes were supplied through a nasogastric tube 4 h after the morning meal. The diet provided had a forage:concentrate ratio of 70:30, composed of coastcross hay and commercial concentrate, with an estimated consumption of 2% of body weigth (BW). Horses received 116 mg/kg of BW of commercial mineral salt mixed in the concentrate. Samples of blood, urine and digesta were collected over a 12 h period after supplementation for analysis of sodium, potassium, chloride, calcium and magnesium concentration. Water intake and urine output were also measured. Electrolytic supplementation enhanced (P<0.05) the water intake, water retention and urine output. Blood variables were not altered by electrolyte supplementation (P>0.05). The supplementation also influenced the sodium and chloride excretion in urine (P<0.05). Urine physicochemical characteristics and the concentration of electrolytes excreted with time were significantly altered as a function of the electrolytes supplementation.